2020
DOI: 10.51791/njap.v46i2.47
|View full text |Cite
|
Sign up to set email alerts
|

Livestock production as an integral of home garden in Nigeria

Abstract: Globally, hunger and poverty are major challenges with number of household malnourished increasing daily. Conscious integration of the home gardens strategy into peri-urban and urban development can help to achieve food security. In this regard, a total of 412 questionnaires were administered to home garden owners around the National Horticultural Research Institute (NIHORT) in Ibadan (Southwest Nigeria), Mbato (Southeast Nigeria), Bagauda (Northwest Nigeria) and Dadinkowa (Northeast Nigeria). In all, 366 (88.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Likewise, since 24 February 2022 till 31January 2023, 18,159,214 Ukrainians crossed the borders into neighbouring countries (Bulgaria, Czech Republic, Romania, Slovakia, Moldova, Hungary and Poland). As many as 5,352,000 people were estimated to be internally displaced in Ukraine as on 23 January 2023, according to Internal Displacement Monitoring Centre (IDMC) 10 quoting IOM(2023).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, since 24 February 2022 till 31January 2023, 18,159,214 Ukrainians crossed the borders into neighbouring countries (Bulgaria, Czech Republic, Romania, Slovakia, Moldova, Hungary and Poland). As many as 5,352,000 people were estimated to be internally displaced in Ukraine as on 23 January 2023, according to Internal Displacement Monitoring Centre (IDMC) 10 quoting IOM(2023).…”
mentioning
confidence: 99%
“…The Ministry of Environmental Protection and Natural Resources ofUkraine (2017) reported 60 protected sites being affected in eastern Ukraine. The war affected heavily the biological diversity and declining rare animal and bird species.Early(2023) has reported that more than 600,000 hectares of wetland are under threat from this war. Of such watershed, 16 ecosystems are designated as Ramsar sites for the international importance of its unique biodiversity and birdlife.…”
mentioning
confidence: 99%
“…Likewise, since 24 February 2022 till 31January 2023, 18,159,214 Ukrainians crossed the borders into neighbouring countries (Bulgaria, Czech Republic, Romania, Slovakia, Moldova, Hungary and Poland). As many as 5,352,000 people were estimated to be internally displaced in Ukraine as on 23 January 2023, according to Internal Displacement Monitoring Centre (IDMC) 10 quoting IOM(2023).…”
mentioning
confidence: 99%
“…The Ministry of Environmental Protection and Natural Resources ofUkraine (2017) reported 60 protected sites being affected in eastern Ukraine. The war affected heavily the biological diversity and declining rare animal and bird species.Early(2023) has reported that more than 600,000 hectares of wetland are under threat from this war. Of such watershed, 16 ecosystems are designated as Ramsar sites for the international importance of its unique biodiversity and birdlife.…”
mentioning
confidence: 99%